Comparison of Fe–Al-modified natural materials by an electrochemical method and chemical precipitation for the adsorption of F− and As(V). Issue 5 (3rd March 2016) - Vázquez Mejía, G.; Martínez-Miranda, V.; Fall, C.; Linares-Hernández, I.; Solache-Ríos, M.
ABSTRACT: The adsorption of fluoride and arsenic ions by modified natural materials may have an impact on the removal of F − and As(V) from waters. In this work, a zeolitic material and pozzolan (commonly known as pumicite) were modified with aluminium an iron by an electrochemical method and chemical precipitation, respectively. The adsorbents were characterized by X-ray diffraction, scanning electron microscopy with energy X-ray disperse spectroscopy analysis and the point of zero charge (pHzpc ). F − and As(V) adsorption properties of both materials were investigated. Adsorption kinetic data were best fitted to pseudo-second-order model and equilibrium data to the Langmuir isotherm model. The highest F − and As(V) sorption capacities were obtained for modified zeolitic (0.866 mg/g) and pozzolan (3.35 mg/g) materials, respectively, with initial F − or As(V) concentrations of 10 mg/L. It was found that the unmodified materials did not show either adsorption of F − ions or As(V), which indicated that Al and Fe in the adsorbents are responsible for the adsorption of these ions. In general, both modified materials show similar capacities for the adsorption of F − and As(V).